Comparative study of hematological parameters of Colossoma macropomum anesthetized with benzocaine and eugenol by using different anticoagulants - Sousa, Andria Gama; Pacheco, Acácio H. B.; Siqueira-Pinto, Gilson A.; dos Reis, Gleika T. J.; Fugimura, Michelle M. S.; Vaz, Luciano J.; Marcusso, Paulo F.; Ramos-Espinoza, Fernando C. [UNESP]; da Silva Claudiano, Gustavo (Springer Nature, 2021)
The objective of the present study was to evaluate the action of benzocaine and eugenol over anesthesia stages and the use of three anticoagulants (ethylenediamine tetraacetic acid, sodium citrate, and sodium heparin) over hematological and biochemical parameters and erythrocyte osmotic fragility in tambaquis Colossoma macropomum. For that, fish were distributed into two experimental groups: G1: fish anesthetized with benzocaine and G2: fish anesthetized with eugenol. Induction and recovery times of anesthesia were evaluated and blood samples with different anticoagulants were collected for hematological and biochemical analysis and osmotic erythrocyte osmotic fragility. Fish anesthetized with eugenol showed a longer period of anesthesia, shorter induction time, and longer recovery time. In addition, fish anesthetized with benzocaine by using sodium citrate showed leukopenia and lymphopenia and morphological alterations when compared to the other anticoagulants. Furthermore, fish anesthetized with eugenol by using sodium citrate showed significantly lower values (P < 0.05) of hematocrit and hemoglobin when compared to other anticoagulants and there were significant differences in erythrocyte osmotic fragility between anticoagulants in fish anesthetized with eugenol. The results observed in this study indicate that eugenol is a good alternative as anesthetics for tambaquis when compared to benzocaine because of its rapid anesthesia induction and few alterations in blood parameters. In addition, the use of EDTA facilitates the erythrocyte conservation and cause few blood alterations compared to other anticoagulants.
Keywords: Anesthesia; Ethylenediamine tetraacetic acid; Sodium citrate; Sodium heparin; Tambaqui